Learning the rules of the game: How is corporate masculinity learned and enacted by male professionals from nonprivileged backgrounds?. Issue 1 (27th October 2020) - Giazitzoglu, Andreas; Muzio, Daniel
Abstract: Focusing on the lived intersection of social class and hegemonic masculinity, this article uses data elicited over a 5‐year period to analyze the experiences of 10 white male participants from nonprivileged socioeconomic backgrounds, who were recruited as information technology professionals by a prestigious professional service firm (PSF). Employing a Bourdieusian perspective, we reveal how participants learned to enact the configuration of corporate masculinity deemed hegemonic in the field of their employing PSF. We pay particular attention to how participants engaged with distinctive forms of cultural capital to enact corporate masculinity, and the symbolic violence and "hidden injuries of class" this represents and leads to. In turn, we highlight how classed masculine norms create exclusion, marginalization, and discrimination in organizations. We suggest that class becomes recognized as a germane area for scholars of diversity and inequality to focus on and integrate in the future, in their ongoing investigations into which social norms create marginalization in organizations.